2007
DOI: 10.1038/ismej.2007.102
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lysogeny (prophage induction) in heterotrophic bacterial and Synechococcus populations in the Gulf of Mexico and Mississippi river plume

Abstract: Lysogeny has been documented as a fundamental process occurring in natural marine communities of heterotrophic and autotrophic bacteria. Prophage induction has been observed to be prevalent during conditions of low host abundance, but factors controlling the process are poorly understood. A research cruise was undertaken to the Gulf of Mexico during July 2005 to explore environmental factors associated with lysogeny. Ambient physical and microbial parameters were measured and prophage induction experiments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 44 publications
3
24
1
2
Order By: Relevance
“…An indirect confirmation that at T4 bacteria in A were more P-limited compared to SD could be the higher frequency of lysogenic cells, along with the particularly low bacterial production and growth rate. A negative relationship between bacterial production and the fraction of lysogenic cells has been found in natural and experimental conditions (Jiang and Paul, 1996;Long et al, 2008); it has been suggested that lysogeny is a prevalent viral life cycle under conditions that do not favor the growth of the hosts (Williamson et al, 2002;Weinbauer et al, 2003a). In our experiment, more lysogenic cells were measured in A compared to SD and the controls 4 days after deposition, suggesting that conditions were less favorable for the growth of the hosts at that time.…”
Section: Methodsmentioning
confidence: 46%
“…An indirect confirmation that at T4 bacteria in A were more P-limited compared to SD could be the higher frequency of lysogenic cells, along with the particularly low bacterial production and growth rate. A negative relationship between bacterial production and the fraction of lysogenic cells has been found in natural and experimental conditions (Jiang and Paul, 1996;Long et al, 2008); it has been suggested that lysogeny is a prevalent viral life cycle under conditions that do not favor the growth of the hosts (Williamson et al, 2002;Weinbauer et al, 2003a). In our experiment, more lysogenic cells were measured in A compared to SD and the controls 4 days after deposition, suggesting that conditions were less favorable for the growth of the hosts at that time.…”
Section: Methodsmentioning
confidence: 46%
“…It has previously been predicted that highly virulent lytic phages will take advantage of r-strategist hosts when they become transiently numerically abundant, whereas slowgrowing members of the community will be infected by less virulent and possibly nonlytic phages (20). Lysogeny has been shown to depend on host growth rate (21), and copiotrophic environments have been generally found to have a higher frequency of infected cells and phage causing larger lytic burst sizes compared with oligotrophic environments (22).…”
Section: Resultsmentioning
confidence: 99%
“…This difference is probably due to variation in the proportion of grazers that are able to consume small cyanobacterial cells, or due to higher abundances of cyanobacteria within Mobile Bay in the summer. Although viruses infecting cyanobacteria are commonly found in marine waters (Suttle & Chan 1993, 1994, Long et al 2008), lysis of cyanobacteria was not detected. For peridinin, grazing was never detected; however, viral lysis may play a role in controlling the abundance and growth of this group.…”
Section: Patterns Of Growth Grazing and Viral Lysismentioning
confidence: 99%